2012
DOI: 10.1590/s0102-09352012000200028
|View full text |Cite
|
Sign up to set email alerts
|

Confiança e agregação de valor em carnes com indicação geográfica

Abstract: Universidade Federal do Rio Grande do Sul -UFRGS -Porto Alegre, RS RESUMOO aumento da procura por produtos agroalimentares com certificação relacionada à origem geográfica tem ocorrido, buscando atender nichos específicos de mercado. Nesse sentido, este trabalho identificou a percepção dos consumidores brasileiros com relação às indicações geográficas e sua disposição em pagar por esse atributo. Como método, realizou-se uma survey utilizando-se o software Sphinx, via internet, com 272 consumidores de carne bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
2
4
0
17
Order By: Relevance
“…With regard to product certification, the data support the statements of Brandão et al (2012) in their study on increased demand for products with certified geographical origins. According to these authors, consumers consider the geographical origin of meat to be an indicator of quality and are willing to pay more for meat possessing this differentiation.…”
Section: Resultssupporting
confidence: 74%
“…With regard to product certification, the data support the statements of Brandão et al (2012) in their study on increased demand for products with certified geographical origins. According to these authors, consumers consider the geographical origin of meat to be an indicator of quality and are willing to pay more for meat possessing this differentiation.…”
Section: Resultssupporting
confidence: 74%
“…These percentages represent the characterization of the age of the Brazilians people. The studies carried out with meat consumers in Brazil, show age percentages very close of observed in this study, because it is the economically active population (Brandão, Ceolin, Canozzi, Revillion, & Barcellos, 2012;Eiras et al, 2017;Souki, Salazar, Antonialli, & Pereira, 2011).…”
Section: Characterization Of Participantssupporting
confidence: 83%
“…Thus, the sum of individuals who consume beef 3 or 4 times a week is 82%. According to Brandão et al (2012) the meat consumption can be considered high when it is superior to 3 times a week, demonstrating that the interviewees in this study have high meat consumption. According to Kirinus et al (2013) current socio-economic changes and the increase on the salary of Brazilian population consequently is reflected as an increase on beef consumption decreasing other basic aliment as rice or bean.…”
Section: Consumption Habitsmentioning
confidence: 64%
“…Estudando a carne certificada na Espanha, Angulo e Gil (2007) citam que a restrição orçamentária dos consumidores limita a premiação das carnes certificadas por meio do pagamento de maior preço. Pesquisando carne com indicação geográfi-ca, Brandão et al (2012) observaram que 65,4 % dos consumidores entrevistados Apenas na questão 3, que arguia os agentes sobre a pessoa que poderia passar informação sobre qualidade da carne aos consumidores, foi observada uma resposta discrepante do gerente de compra de gado em relação aos demais agentes. Nas demais questões e entre os demais agentes, conforme já discutido na tabela VIII, se observa relativa uniformidade nas respostas às questões abordadas nesta pesquisa (figura 7).…”
Section: Tabela IV Fonte De Informação Mais Importante Como Indicadounclassified